2003
DOI: 10.1021/ie021044e
|View full text |Cite
|
Sign up to set email alerts
|

Phase Inversion in Abnormal O/W/O Emulsions. 2. Effect of Surfactant Hydrophilic−Lipophilic Balance

Abstract: The effect of surfactant hydrophilic−lipophilic balance (HLB) on the catastrophic phase inversion of an emulsion, and the internal structure of the drops, was studied by using a model abnormal O/W/O emulsion. The system was composed of polyisobutylene, water, and a mixture of a water-soluble and an oil-soluble surfactant. The abnormal O/W/O emulsions were made by gradual addition of water to the oil in the presence of surfactant until the catastrophic phase inversion to the corresponding normal O/W emulsions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 20 publications
1
27
0
5
Order By: Relevance
“…41 We refer the readers interested in catastrophic phase inversion to seminal studies focusing on this important topic. 22, [42][43][44][45][46][47][48][49][50][51][52][53][54][55] …”
Section: Introductionmentioning
confidence: 99%
“…41 We refer the readers interested in catastrophic phase inversion to seminal studies focusing on this important topic. 22, [42][43][44][45][46][47][48][49][50][51][52][53][54][55] …”
Section: Introductionmentioning
confidence: 99%
“…This is because concentration is not the only variable related to surface-active components that should be considered: its affinity toward a given phase and how it changes with operating conditions also play substantial roles. [60,61] Morphology For each reaction, samples before and after the apparent viscosity minima were observed by TEM, to verify the occurrence of the inversion phenomenon. As an example, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior may be caused by the reduction in the HLB of the surfactant [6]. In many reports, it is reported that HLB decreases with cosurfactant concentration [35][36][37]. The microstructure of the microemulsion can transform from Winsor type I to type III, and subsequently into phase II with decreasing surfactant HLB [38].…”
Section: Effect Of Co-surfactant Concentrationmentioning
confidence: 99%